DESIGN AND IMPLEMENTATION OF ACTUATOR NODE IN EVAPOTRANSPIRATION-BASED IRRIGATION SCHEDULING SYSTEM - Kinguantoro, Kevin
In agriculture, farming can be done outdoors, which is done in open field, or indoors, which can be done in a screen house. Irrigation becomes important both in indoor and outdoor farming, because this process returns the amount of water loss on plants, the water needs in plant can be fulfilled. This process becomes more important especially in dry season, when rain rarely occurs, because unfulfilled water needs can interfere with the plant growth. However, excessive irrigation can also interfere with the plant growth. Therefore, it is necessary to determine the amount of water needed by plants to avoid this. There are several ways to determine the amount of water needed, one of which is by determining reference evapotranspiration. In determining the reference evapotranspiration, weather data from time to time is needed, namely temperature, humidity, solar irradiation, and wind speed. As the weather changes, the evapotranspiration value also changes. After determining the amount of water needed, each plant needs to be given the same amount of water. However, the amount of water given sometimes may vary due to human errors. For that, a tool that is able to provide water automatically to plants with the same amount of water as the plant’s water needs is needed. For this reason, in this research, a tool that can assist the irrigation process in designed in the form of an actuator node that can regulate the water flow. The actuator node has a main function of opening/closing a valve. The valve is connected to a flow sensor which is used to measure the amount of water that has flowed through the valve so it does not exceed the amount of water required. This tool communicates wirelessly with a gateway to collect the data on the amount of water needed, and it requires a power source which is rechargeable.